2016
DOI: 10.1055/s-0035-1571264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sacrospinous Colpopexy Associated with Anterior Colporrhaphy for the Treatment of Dome Prolapse on all Three Vaginal Compartments

Abstract: In this retrospective study, the surgical correction of vault prolapse using a sacrospinous ligament fixation technique associated with anterior colporrhaphy proved effective in resolving genital prolapse. Despite the low complication rates, there was a high rate of cystocele, which may be caused by posterior vaginal shifting due to either the technique or an overvaluation by the POP-Q system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
1
0
5
Order By: Relevance
“…In a study by De Castro et al, 12 buttock pain was reported as the commonest. Evaluating the vaginal vault after a year revealed that 95% of the patients were in stage zero and that 5% were in stage 1.…”
Section: Discussionmentioning
confidence: 96%
“…In a study by De Castro et al, 12 buttock pain was reported as the commonest. Evaluating the vaginal vault after a year revealed that 95% of the patients were in stage zero and that 5% were in stage 1.…”
Section: Discussionmentioning
confidence: 96%
“…Normalmente indicado para mulheres que apresentam POP em estágios mais avançados (III e IV) que optam por não realizar a cirurgia, por não apresentar em condições clínicas, ou mesmo por estarem aguardando tratamento cirúrgico [8,9]. Já quando o método cirúrgico é necessário, os objetivos principais são a restauração anatômica da região pélvica, bem como a manutenção da função sexual, urinária, intestinal e prevenção da recorrência do POP [10]. Entre os tratamentos cirúrgicos atuais encontram-se a colpopexia sacral abdominal, colpopexia sacroespinhal vaginal, colposacropexia laparoscópica, uso de telas de polipropileno, malha transvaginal, histerectomia vaginal e histeropexia [10][11][12][13].…”
unclassified
“…Já quando o método cirúrgico é necessário, os objetivos principais são a restauração anatômica da região pélvica, bem como a manutenção da função sexual, urinária, intestinal e prevenção da recorrência do POP [10]. Entre os tratamentos cirúrgicos atuais encontram-se a colpopexia sacral abdominal, colpopexia sacroespinhal vaginal, colposacropexia laparoscópica, uso de telas de polipropileno, malha transvaginal, histerectomia vaginal e histeropexia [10][11][12][13]. Cada um desses métodos representa uma escolha em relação ao tipo de POP que o paciente apresenta.…”
unclassified
“…Однако традиционно выполняемая кольпоррафия со-провождается высокой частотой рецидивов, достигающей в случае коррекции цистоце-ле, по данным некоторых авторов, 70 % [26]. Описано исследование, результаты которого свидетельствуют о низкой эффективности передней кольпоррафии как превентивного метода в отношении цистоцеле de novo после крестцово-остистой фиксации [27]. Последнее может быть объяснено техникой традицион-ной кольпоррафии, заключающейся в нало-жении отдельных рассасывающихся швов на наружную поверхность влагалищной фасции.…”
unclassified